LOW VELOCITY AND LOW ELECTRICAL RESISTIVITY LAYERS IN THE MIDDLE CRUST - Pavlenkova N.I. (My University, 2004)
Some Deep Seismic Sounding (DSS) revealed low velocity layers in the upper and middle crust of old platforms. The layers are often characterised by a lower electrical resistivity. It is not clear, however, how reliable the layers recognized from DSS data are, if they are regular or occasional events and how they correlate with other geophysical parameters. To answer these questions the experimental DSS data obtained in the Baltic and Ukranian shields by different institutions were reinterpreted by the author with unified methods. The shield areas are well studied using both the DSS and high-frequency magnetotelluric sounding (MTS) methods. As a result a marked velocity inversion (waveguide) was observed in a 10 to 20 km depth range in the majority of the DSS profiles. An increase in the electrical conductivity is typical for the waveguide. A comparison of the results with the data from other platform regions allow the conclusion that this low velocity and high electrical conductivity layer has a global significance. In the continental crust, the layer is characterised by changes in the reflectivity pattern, earthquakes number and changes in velocity pattern where the block structure is transformed into a subhorizontal layering. These structural features suggest that the layers separate brittle and weak parts of the crust. Usually they play the role of detachment zones at crustal block moving. A possible factor responsible for this phenomenon is an increase in porosity and in the salinity of the waveguide pore water compared with the upper crust. This suggestion is confirmed by the Kola superdeep borehole data. Porosity increasing in the middle crust is explained by the change in rock mechanical properties with depth, by fracturing porosity and by dilatancy effect, at a depth of 10-20 km.